Two Approaches for Promoting Student Centered Language Learning: Cooperative Learning and Positive Psychology - Jacobs, George; Chau, Meng Huat (Widya Mandala Catholic University Surabaya, 2021)
This article links two approaches to promoting less competitive, more positive, and more student centered learning environments for language learners: cooperative learning and positive psychology. The article begins by explaining each of these two approaches. First, the article provides background, including research support, for cooperative learning and explains eight cooperative learning principles: maximum peer interactions, equal opportunities to participate, individual accountability, positive interdependence, group autonomy, heterogeneous grouping, teaching collaborative skills, and cooperation as a value. Second, the article supplies similar background, including research support, for positive psychology, including seven principles: relationships with others, responsibility, gratitude, positivity, strengths, kindness, and meaning. The article’s next section explores links between cooperative learning and positive psychology in language education and explains that the use of positive psychology in education frequently uses the name positive education. Then, the article presents an extensive reading activity and explains how the design of the activity draws on the eight cooperative learning principles and the seven positive psychology principles. Finally, the article explains how both cooperative learning and positive psychology support student centered language learning, and presents a student centered intensive reading activity that draws on the same eight cooperative learning principles and seven positive psychology principles.